The effectiveness and safety of lifestyle medicine and integrative therapies in inflammatory arthritis: an umbrella review using a hierarchical evidence gathering approach - Lin, Joshua; Liu, Jing; O’Fee, Allana; Pandey, Chhiti; Benna-Doyle, Sarah; Maunder, Alison; Rao, Vibhuti; Alesi, Simon; Ng, Beverly; Ee, Carolyn (Frontiers in Medicine, 2024)
Objective An umbrella review was conducted to provide a comprehensive evaluation of the evidence on lifestyle medicine and integrative therapies for inflammatory arthritis. Methods Five electronic databases were searched for umbrella reviews, meta-analyses, and systematic reviews of randomised controlled trials on acupuncture, diet, exercise, herbal medicine, nutrient supplements, and mind–body therapies for rheumatoid arthritis, spondyloarthritis, and gout published from January 2012 to December 2022. The primary outcomes were functional status and quality of life. Quality assessment was performed using the A MeaSurement Tool to Assess systematic Reviews (AMSTAR-2) tool, and the certainty of evidence for our primary outcomes was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach where possible. Results We included 52 reviews. Exercise was beneficial for functional status in both rheumatoid arthritis and spondyloarthritis, with moderate certainty of evidence. Chinese herbal medicine in combination with disease-modifying anti-rheumatic drugs may improve functional status in rheumatoid arthritis (very low certainty evidence). Acupuncture may improve functional status in rheumatoid arthritis and pain in both rheumatoid arthritis and gout; however, the evidence is of very low certainty. Evidence for other therapies was not clinically significant; however, it suggests possible benefits from quercetin and polyunsaturated fatty acids. Yoga may result in a moderate improvement in functional status when used as an adjunct to medication; however, the certainty of evidence is very low. Diet interventions offered inconsistent improvements to functional status in rheumatoid arthritis, spondyloarthritis, and gout with low to very low certainty. Conclusion Exercise should be prescribed for people with rheumatoid arthritis and spondyloarthritis. More research is needed to confirm or refute evidence for Chinese herbal medicine, acupuncture, yoga, and anti-inflammatory diets.